Basiliximab treatment for autoimmune bowel disease in a pediatric heart transplant patient. (16th September 2015) - Puri, K.; Kocoshis, S.; Risma, K.; Perez, L.; Hart, C.; Chin, C.; Ryan, T. D.; Jefferies, J. L.; Schumacher, K. R.; Castleberry, C.
Abstract Autoimmune‐mediated bowel disease has been reported after pediatric heart transplantation. Recognition and treatment of these patients has been difficult. We describe a patient who responded to steroids and basiliximab therapy after an inflammatory process secondary to abnormal T‐cell activation. Our patient is a 28‐month‐old female who received a heart transplant at five wk of age. At 24 months post‐transplant, she developed fever and bloody stools. Initial investigations were significant for an elevated ESR (>120) and CRP (15.2). Symptoms persisted despite bowel rest and mycophenolate discontinuation. Endoscopic evaluation revealed discontinuous ulcerative disease involving esophagus, terminal ileum, right and left colon, necessitating extensive bowel resection. She had additional airway inflammation leading to a TEF at the site of esophageal ulceration, requiring tracheostomy. Immune evaluation revealed autoimmune dysregulation that responded to parenteral methylprednisolone. Chronic basiliximab therapy allowed for successful weaning of steroids with sustained remission. She has been transitioned to sirolimus and tacrolimus maintenance immunosuppression with plans to discontinue basiliximab once off steroids. In conclusion, bowel disease in the setting of pediatric heart transplantation can be severe and refractory to traditional treatment methods. Tailoring immune therapy to activated T cells can result in remission. Basiliximab therapy was used in our patient to maintain steroid‐induced remission, but long‐term complications of this disease process are unknown.